Evaluation of South African Chenin Blanc Wines Made From Six Different Trellising Systems Using a Chemical and Sensorial Approach - Panzeri, V.; Ipinge, H.N.; Buica, A. (South African Journal of Enology and Viticulture, 2020)
There are many ways of manipulating the components of grape berries and one of these is the implementation of a specific trellising system. This will affect light exposure in the bunch zone, air flow through the canopy, crop load, etc., and consequently the primary metabolites that contribute to the production of secondary compounds in wine. The aim of the present study was to characterise the grape musts and wines of Chenin blanc made from grapes of different trellising systems, using chemical fingerprinting of the samples and the check-all-that-apply method, combined with a quality scoring test. The results indicate that, while the wines could not be separated according to treatment from an aroma point of view, the grapes produced by different trellis systems resulted in wines characterised by differences in taste and mouthfeel. The present study shows that trellising systems can influence amino acids, yeast assimilable nitrogen, phenolic content and aroma compounds, as well as sensory characteristics. In this case study, wine quality was not affected by the trellising systems, with one exception. Fingerprinting using high-resolution mass spectrometry proved to be a successful tool to separate the samples according to the systems.